2023
DOI: 10.1098/rsos.230783
|View full text |Cite
|
Sign up to set email alerts
|

Looming-eyes buoys fail to reduce seabird bycatch in the Icelandic lumpfish fishery: depth-based fishing restrictions are an alternative

Yann Rouxel,
Hólmfríður Arnardóttir,
Steffen Oppel

Abstract: Bycatch in gillnets from lumpfish ( Cyclopterus lumpus ) fisheries is an important conservation issue in the north Atlantic, with up to 30 000 seabirds potentially killed each year. To date, no technical solutions exist to reduce the bycatch of seabirds in gillnet fisheries, but research on above-water bird deterrents as a form of bycatch mitigation has shown promising results. Here, we tested whether a floating device called ‘looming-eyes buoy’ (LEB) would consistently reduce the bycat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 36 publications
1
12
0
Order By: Relevance
“…morhua), which shows that some seabird bycatch even occurs in waters greater than 50 m deep, which complements the data obtained in our study focussed only on the lumpfish fishery [3]. Unfortunately, Kennedy & Sigurðsson [4] did not present data on marine mammal bycatch, which peaked at intermediate depths in our study [3] and should be considered when exploring solutions to reduce non-target bycatch in the Icelandic lumpfish fishery [5].…”
supporting
confidence: 78%
See 1 more Smart Citation
“…morhua), which shows that some seabird bycatch even occurs in waters greater than 50 m deep, which complements the data obtained in our study focussed only on the lumpfish fishery [3]. Unfortunately, Kennedy & Sigurðsson [4] did not present data on marine mammal bycatch, which peaked at intermediate depths in our study [3] and should be considered when exploring solutions to reduce non-target bycatch in the Icelandic lumpfish fishery [5].…”
supporting
confidence: 78%
“…In an attempt to develop solutions to this problem, we recently tested whether a bird-scaring device could reduce seabird bycatch in the Icelandic lumpfish (Cyclopterus lumpus) fishery, which kills an estimated 8000 seabirds annually [2]. This investigation showed that the device was ineffective, but that seabird and marine mammal bycatch could be virtually eliminated if (i) lumpfish fisheries were restricted to waters greater than 50 m deep, and (ii) the patterns we found in our study area would apply to other fishing areas around Iceland [3]. We acknowledged that further research was necessary to explore whether the fish catch and bycatch patterns we found in our study area were representative of all of Iceland and that socio-feconomic considerations were necessary before any fishery restrictions could be imposed.In a welcome contribution to work towards solutions for the bycatch problem in the Icelandic lumpfish fishery, Kennedy & Sigurðsson [4] now present novel data that shed further light on some of our assumptions.…”
mentioning
confidence: 99%
“…The bycatch of birds in bottom set gillnets in Iceland is recognized as an issue, with several technical solutions being proposed and trialled, but so far, without success [1,2]. Using data collected during an investigation on whether 'looming eyes' buoys could reduce bycatch in lumpfish (Cyclopterus lumpus) gillnets, Rouxel et al [1] proposed 'that limiting fishing to waters more than 50 m deep could save between 5000 and 9300 seabirds every year, arrest the population decline of endangered black guillemots (Cepphus grylle) in Iceland, while having only a marginal effect on target fish catch'. This is an interesting result and if this is indeed the case has potential to improve the environmental impact of this fishery.…”
mentioning
confidence: 99%
“…This is an interesting result and if this is indeed the case has potential to improve the environmental impact of this fishery. The study by Rouxel et al [1] was based upon the catches of 84 fishing trips from 7 vessels, of which 21 fishing trips from 3 fishing vessels fished at a depth >50 m, with one boat accounting for 10 of these trips. The study took place in Húnaflói Bay, in northern Iceland (figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation